Independence of the Indonesian Constitutional Court in Norms and Practices - Eddyono, Luthfi Widagdo (The Constitutional Court of the Republic of Indonesia, 2017)
Article 24 (1) of the 1945 Constitution States after the third amendment, âthe judicial power shall be independent in administering justice so as to uphold the law and equality.â The Indonesian Constitutional Court is one of the performers of the independent judicial power who plays a significant role in the enforcement of the constitution and the principle of the state based on the law by its authority and obligations as determined by the 1945 Constitution. This paper intends to study the Indonesian Constitutional Court to find out whether the Constitutional Court in exercising its constitutional authority can be independent. Also, this article will examine not just institutional independence but also judges independence to understand current issues related to the role of ethics and conduct of judges. The independence of the Indonesian Constitutional Court supported by the 1945 Constitution after the amendments from 1999 until 2002, and further stipulated in Law. However, it can be said that this institution has ups and downs of public trust due to corruption cases conducted by constitutional justices. Also, in several political instances showed efforts of political institutions to limit the authority of the Constitutional Court. In its experiences, the Constitutional Court succeeded in convincing the parties through its decisions and strengthening institutional independence against the influence that tried to destabilize its institutions. The Council of Ethics of Constitutional Judges that maintains the values and behavior of judges also continuously works and efficient enough in overseeing the ethics and conduct of judges. The decision of the Ethics Council may also be accepted as a proportional decision.